Fast-strength long-acting high-toughness high-elasticity waterproof bonding layer material and preparation method thereof

By adopting a waterproof bonding layer material with a multi-component system, using asphalt, epoxy resin and other materials, combined with high-speed shear, stirring and ultrasonic dispersion processes, the existing waterproof materials have complex construction technology, long curing time and poor adaptability. The problem is that the material is quickly cured, high bond strength and durability are achieved, and is suitable for the high-performance waterproofing needs of modern engineering.

CN119463806APending Publication Date: 2025-02-18SHANGHAI TONGZHOU INTELLIGENT TRANSPORTATION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411386459.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing waterproof materials have problems in complex construction processes, long curing time, poor adaptability, etc., which are difficult to meet the needs of modern engineering for high-performance waterproof bonding layer materials.

Method used

Using a multi-component system composed of asphalt, epoxy resin, butadiene-styrene-butadiene block copolymer, polyethylene oxide, liquid rubber, nano zinc oxide powder and crosslinking agent, through high-speed shearing , stirring and ultrasonic dispersion processes to prepare fast, strong, long-term, high toughness, and high elastic waterproof bonding layer materials.

Benefits of technology

It realizes rapid curing of the material, improves bonding strength and durability, enhances the toughness and elasticity of the material, simplifies the construction process, and significantly improves the adaptability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention relates to a fast-strength long-acting high-toughness high-elasticity waterproof bonding layer material and a preparation method thereof. An asphalt component and an epoxy material component are taken as main bodies of the bonding material. In order to realize the characteristics of a high-toughness and high-elasticity bonding layer, a modifier needs to be added into an asphalt component. As a waterproof binding material which can be used at normal temperature, the stability and dispersibility of asphalt components need to be ensured, so that the construction workability of the waterproof binding material is ensured. In consideration of application of the waterproof binding material in road engineering and constructional engineering, the waterproof binding material needs to have the characteristics of early strength and quick drying, so that the influence of curing time on construction is reduced, and particularly, the requirement of opening traffic as soon as possible in road engineering construction can be met. In addition, the waterproof binding material needs to have the long-acting and durable advantages, the diluted asphalt subjected to compound modification of the butadiene-styrene-butadiene segmented copolymer, the polyoxyethylene and the liquid rubber is selected to be subjected to cross-linking combination with the epoxy material, and the curing agent is added to achieve the short-term curing effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a ratio of the modified waterproof adhesive layer and a preparation method thereof, and in particular to a fast-strengthening, long-acting, high-toughness and high-elastic waterproof adhesive layer material and a preparation method thereof. Background Art

[0002] The present invention relates to a ratio and preparation method of a modified waterproof adhesive layer material, which is particularly suitable for the field of high-demand construction and road engineering. The waterproof adhesive layer material is widely used in the fields of roads, buildings, waterproof repairs, tunnels and underground engineering. It not only needs to have excellent waterproof performance, but also needs to have excellent adhesion, toughness and elasticity to cope with structural deformation and environmental stress. However, traditional waterproof materials often have problems such as insufficient durability, insufficient adhesion, poor crack resistance, etc., which are difficult to meet the needs of modern engineering for long-term protection.

[0003] In order to solve these problems, the research and development of modified waterproof adhesive materials has gradually become a technical hotspot in recent years. By introducing enhanced modifications such as polymer materials and nanomaterials, researchers are committed to improving their strength, toughness, elasticity and anti-aging properties. Compared with traditional materials, modified waterproof materials have significantly improved in durability, flexibility, elasticity and anti-aging properties. However, existing modified materials still face some problems in practical applications:

[0004] (1) Complex construction process

[0005] Although the research and development of modified waterproof materials has improved the performance of materials, their complex preparation process and construction requirements have also increased the difficulty of construction. Some modified materials have strict requirements on environmental conditions such as construction temperature and humidity. If they are not properly operated, the final waterproof effect may be affected. This brings greater challenges to construction workers and also limits the operability of modified materials in a wide range of applications.

[0006] (2) It is difficult to achieve both durability and fast curing

[0007] While pursuing fast curing and convenient construction, how to ensure the durability and waterproof performance of the material is a major technical challenge. Fast-curing waterproof materials often show problems of insufficient strength or poor weather resistance in long-term use, while materials that focus on durability often require longer curing time, thus delaying the progress of the project. Therefore, developing a material that combines fast curing, excellent durability and elasticity has always been a core challenge in the field of waterproof materials.

[0008] (3) Poor adaptability of waterproof materials

[0009] Existing modified waterproof materials have poor adaptability when facing different substrates and complex construction conditions. For example, some materials perform well on concrete surfaces, but it is difficult to achieve ideal waterproofing effects on substrates such as metal or wood. This lack of adaptability has limited the application of modified waterproof materials in a variety of construction projects.

[0010] In summary, although the performance of modified waterproof materials is improved compared to traditional materials, they still have not completely solved the problems of difficult construction, long curing time, and poor adaptability. In order to further meet the high performance requirements of the road and construction industries for waterproof bonding layer materials, it is particularly important to develop a waterproof bonding layer material that is quick-drying, strong, long-lasting, and has both high toughness and high elasticity. The present invention is based on the deficiencies of the prior art and proposes a waterproof bonding material with fast curing, high toughness, high elasticity, and long-term durability through innovative formula design and preparation methods, aiming to provide a more efficient and reliable waterproof solution for roads and construction projects. Summary of the invention

[0011] The purpose of the present invention is to overcome the defects of the above-mentioned existing waterproof materials and technologies and to provide a fast-strengthening, long-lasting, high-toughness and high-elastic waterproof bonding layer material and its preparation method, so as to solve the problems of ordinary traditional waterproof materials such as high preparation requirements, complex construction process, long time required for opening traffic, and poor long-term effectiveness.

[0012] The purpose of the present invention can be achieved by the following technical solutions:

[0013] A fast-strengthening, long-lasting, high-toughness, high-elastic waterproof adhesive layer material, the raw materials of which include the following components in parts by weight:

[0014] Component A:

[0015]

[0016]

[0017] Component B:

[0018]

[0019] Component C:

[0020] Pentaerythritol triallyl ether

[0021] Component D:

[0022] Trimellitic anhydride

[0023] The weight ratio of component A to component B is 1:1.2-1:1.5, the weight of component C is 5% of component A, and the weight of component D is 3%-5% of component B.

[0024] The waterproof bonding material of the present invention involves several different components, among which the asphalt component and the epoxy material component are the main body of the bonding material. In order to achieve the high-toughness and high-elasticity bonding layer characteristics, it is necessary to add a modifier to the asphalt component. As a waterproof bonding material that can be used at room temperature, it is necessary to ensure the stability and dispersibility of the asphalt component to ensure its construction and workability. Considering the application of waterproof bonding materials in road engineering and construction engineering, it is necessary to have the characteristics of early strength and fast drying to reduce the impact of curing time on construction, especially to meet the demand for opening traffic as soon as possible in road engineering construction. In addition, the waterproof bonding material also needs to have the advantage of long-term durability.

[0025] In order to achieve the effect of the above waterproof bonding layer material, the present invention selects diluted asphalt modified by butadiene-styrene-butadiene block copolymer, polyethylene oxide and liquid rubber to cross-link and combine with epoxy material, and adds a curing agent to achieve a short-term curing effect.

[0026] The butadiene-styrene-butadiene block copolymer is a linear butadiene-styrene-butadiene block copolymer with a molecular weight of 80,000 to 100,000. The molecular weight of polyethylene oxide is 20,000 to 40,000.

[0027] The liquid rubber is liquid butyl rubber, preferably, the molecular weight of the liquid butyl rubber is 50,000;

[0028] The stabilizer is a sulfur stabilizer.

[0029] Preferably, the average particle size of the nano zinc oxide powder is 16 nm.

[0030] The cross-linking agent is pentaerythritol triallyl ether.

[0031] The curing agent is trimellitic anhydride.

[0032] Preferably:

[0033] The raw materials of a fast-strengthening, long-lasting, high-toughness and high-elastic waterproof adhesive layer material include the following components in parts by weight:

[0034] Component A:

[0035]

[0036] Component B:

[0037]

[0038] Component C:

[0039] Pentaerythritol triallyl ether

[0040] Component D:

[0041] Trimellitic anhydride

[0042] The weight ratio of component A to component B is 1:1.2, the weight of component C is 5% of component A, and the weight of component D is 3% of component B.

[0043] The present invention also provides a method for preparing a fast-strengthening, long-lasting, high-toughness, high-elastic waterproof adhesive layer material, comprising the following steps:

[0044] (1) After heating petroleum asphalt, butadiene-styrene-butadiene block copolymer, polyethylene oxide and sulfur are added to perform high-speed shearing and stirring treatment;

[0045] (2) adding liquid rubber to the material obtained in step (1) and stirring the mixture, and then standing the mixture to develop swelling after stirring and mixing.

[0046] (3) Add sulfonated kerosene to the material obtained in step (2), and stir and dilute to obtain component A.

[0047] (4) Dissolve stearic acid in anhydrous ethanol to form a transparent stearic acid anhydrous ethanol solution. Then add nano zinc oxide powder into the stearic acid anhydrous ethanol solution for dispersion.

[0048] (5) Add epoxy resin to the milky white hydrophobic material solution formed in step (4), and stir to obtain component B.

[0049] (6) Components A and B are mixed, heated and stirred, and then component C is added and stirred. Component D is then added and stirred again.

[0050] (7) The material obtained in step (6) is heated and stirred for a second time to pre-evaporate part of the sulfonated kerosene to obtain the fast-strengthening, long-lasting, high-toughness, high-elasticity waterproof adhesive layer material.

[0051] In step (1), the heating temperature is 150-160° C., the rotation speed of the high-speed shearing machine is 3000-4000 rpm, and the shearing treatment time is 60-80 minutes; the stirrer stirs at a speed of 1000-2000 rpm for 40-60 minutes;

[0052] In step (2), the stirrer stirs at a speed of 1000 rpm for 20 to 40 minutes; the standing development swelling time is at least 2 hours;

[0053] In step (3), the stirrer stirs at a speed of 1000 to 1200 rpm for 20 to 40 minutes;

[0054] In step (4), the dispersion method is to use an ultrasonic disperser for dispersion, and the dispersion time is 10-15 minutes.

[0055] In step (5), the mixer is stirred at a speed of 400-600 rpm for 10 minutes;

[0056] In step (6), the heating temperature is 50-60°C, and the stirring time of component C and component D in the stirrer is 30 minutes respectively, and the stirring speed is 600-800 rpm;

[0057] In step (7), the secondary heating temperature is 50° C., and the stirrer stirs at a speed of 600-800 rpm for 30 minutes.

[0058] Preferably, in step (1), the heating temperature is 160° C., the rotation speed of the high-speed shearing machine is 3000 rpm, and the shearing treatment time is 60 minutes; the stirrer stirs at a constant speed of 1000 rpm for 60 minutes;

[0059] In step (2), the stirrer is stirred at a speed of 1000 rpm for 30 minutes; the standing development swelling time is 24 hours;

[0060] In step (3), the stirrer stirs at a speed of 1000 rpm for 30 minutes;

[0061] In step (4), the dispersion method is to use an ultrasonic disperser for dispersion, and the dispersion time is 10 minutes.

[0062] In step (5), the stirrer is stirred at a speed of 500 rpm for 10 minutes;

[0063] In step (6), the heating temperature is 50°C, and the stirring time of component C and component D in the stirrer is 30 minutes respectively, and the stirring speed is 800 rpm;

[0064] In step (7), the secondary heating temperature is 50° C., and the stirrer stirs at a constant speed of 600 rpm for 30 minutes.

[0065] Compared with the prior art, the present invention has the following beneficial effects:

[0066] (1) The main materials of the present invention are component A (asphalt material) and component B (epoxy resin material). Among them, component A is a modified asphalt substrate, which is compositely modified by using butadiene-styrene-butadiene block copolymer and polyethylene oxide. The polyethylene oxide with a molecular weight of 20,000 to 40,000 used in the present invention can show higher viscosity in asphalt, and has the properties of thickening and dispersion. The addition of polyethylene oxide can increase the viscosity of asphalt while helping to disperse butadiene-styrene-butadiene block copolymer in asphalt. In addition, connection points can be formed in the molecular structure of polyethylene oxide material, which play a role of connection and buffering between the components. When the system is subjected to tension, the network structure formed by these connection points can undergo large deformation, which improves the elasticity and toughness properties of the system. Liquid rubber has good interfacial compatibility, greatly improves the adhesion and affinity of the asphalt system, and has excellent elastic effect and physical properties while having heat and cold resistance effects. The liquid rubber and butadiene-styrene-butadiene block copolymer are compounded and modified to further enhance the elastic strength and low temperature resistance of the asphalt component system. At the same time, the liquid rubber can also improve the compatibility and dispersibility of the component A asphalt system and the component B epoxy system. Sulfonated kerosene has a uniform evaporation rate, less aromatic hydrocarbon content, no odor, no residue after evaporation, is not easily oxidized by heat, has low sulfur, low toxicity, is environmentally friendly, and has strong solubility. It can be used as a good asphalt diluent, making it convenient for the material to be constructed under non-high temperature conditions.

[0067] (2) In component B, epoxy resin is used as the matrix, and a hydrophobic nanomaterial composed of nano zinc oxide powder, stearic acid and anhydrous ethanol is obtained to obtain a nanoparticle / epoxy composite component. This system can provide good strength and durability for waterproof adhesive materials after mixing with component A, and exhibits significant hydrophobicity and deicing performance. After observing component B under a scanning electron microscope (SEM), it can be found that the nano zinc oxide particles are evenly distributed, and the outline of each nanoparticle is clear, showing an irregular surface roughness structure, such as dents and protrusions, which forms a micron-scale rough structure on the surface of component B, thereby enhancing its hydrophobicity.

[0068] (3) After mixing components A and B, add components C and D respectively, and stir them respectively after adding. Pentaerythritol triallyl is a colorless transparent liquid, which is mainly used for crosslinking. It contains three allyl groups and one hydroxyl group, which can quickly crosslink the asphalt component and the epoxy resin component. The asphalt component forms a stable and uniform "liquid network" in the epoxy resin. This is a multi-component interpenetrating network three-dimensional structure, which has the advantages of both epoxy resin and asphalt materials, and retains the high viscosity and high elasticity of the asphalt component and the durable and long-lasting characteristics of the epoxy resin component.

[0069] (4) As a room temperature curing agent, trimellitic anhydride can produce a curing reaction in a relatively short time. The epoxy group is attacked to generate an ester bond and a new alkoxy anion, which can combine with the anhydride molecule to form a new ion pair, and continue to open the epoxy group. The above process of reaction, chain extension, branching and cross-linking can be continuously followed alternately to eventually form a relatively complete epoxy-anhydride cross-linking network. Its application in road waterproof bonding layer or building waterproofing can play the role of early bonding strength and rapid opening for traffic or use.

[0070] (5) Using an ultrasonic instrument to disperse the hydrophobic material (nano zinc oxide powder) instead of ordinary magnetic stirring can greatly shorten the dispersion time. Through infrared spectroscopy experiments, it was found that the ultrasonic dispersion method promoted the grafting of the alkyl group in stearic acid to the surface of zinc oxide particles, and the hydroxyl groups on the surface of nano zinc oxide particles were replaced by the carboxyl groups of stearic acid and existed on the surface of nanoparticles in the form of coordinated adsorption. The new absorption peaks appearing in the infrared spectrum indicate that new chemical bonds may be formed between stearic acid and zinc oxide nanoparticles, rather than simple interface adsorption. This dispersion method promotes the replacement of hydroxyl groups on zinc oxide by rigid esters, making it hydrophobic, which makes zinc oxide nanoparticles more effectively dispersed in the solvent and can reduce the surface energy of the system. The above chemical reaction only occurs in the system obtained by ultrasonic dispersion, and is not found in the samples obtained by ordinary mechanical stirring.

[0071] The content of each component of the fast-strengthening, long-lasting, high-toughness and high-elastic waterproof bonding layer material in the present invention should be within the range mentioned in the technical solution. The range requirements of the content of each component in the technical solution are based on experimental results. If the content of butadiene-styrene-butadiene block copolymer and liquid rubber in component A is too low, the polymer modified material cannot form a stable network structure in the asphalt. If the content of the two is too high, the material cost will increase and the economy of the asphalt component cannot be fully utilized. The ratio of component A asphalt component and component B epoxy material component should also be within the range mentioned in the technical solution. The ratio of the two will affect the compatibility of the asphalt component and the epoxy material component, the stability of the "liquid network" and the final curing effect of the waterproof bonding material. The use of the component content requirements of this solution can reduce the use of additives and cross-linking agents, reduce material costs, and at the same time meet the compatibility of modified materials, petroleum asphalt and epoxy materials, and achieve the unity of performance effect and economy of waterproof bonding materials. DETAILED DESCRIPTION

[0072] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0073] Comparative Example 1

[0074] This comparative example is a multi-component waterproof adhesive layer, which is prepared from the following raw materials in parts by weight: Component A:

[0075]

[0076] Component B:

[0077]

[0078] Component C:

[0079] Pentaerythritol triallyl ether

[0080] Component D:

[0081] Trimellitic anhydride

[0082] The weight ratio of component A to component B is 1:1.2, the weight of component C is 5% of component A, and the weight of component D is 3% of component B.

[0083] The preparation method is as follows:

[0084] After heating the petroleum asphalt to 160°C, polyethylene oxide and sulfur are added for high-speed shearing and stirring. The speed of the high-speed shearing machine is 3000 rpm, and the shearing time is 60 minutes; the stirrer is stirred at a uniform speed of 1000 rpm for 60 minutes. Then sulfonated kerosene is added for dilution, and stirred at a uniform speed of 1000 rpm for 30 minutes to obtain component A. Stearic acid is dissolved in anhydrous ethanol to form a transparent stearic acid anhydrous ethanol solution. Then, nano zinc oxide powder is added to the stearic acid anhydrous ethanol solution, dispersed for 10 minutes using an ultrasonic disperser, and epoxy resin is added. Stir at a uniform speed of 500 rpm for 10 minutes to obtain component B. Components A and B are mixed and heated to 50°C and stirred. Component C is added, stirred at 800 rpm for 30 minutes, and then component D is added and stirred for 30 minutes. Finally, the mixture is heated to 50°C for a second time and stirred at 600 rpm for 30 minutes to obtain a waterproof bonding layer material.

[0085] Comparative Example 2

[0086] This comparative example is a single-component waterproof adhesive layer, which is prepared from the following raw materials in parts by weight:

[0087]

[0088] The preparation method is as follows:

[0089] After heating petroleum asphalt to 160°C, butadiene-styrene-butadiene block copolymer, polyethylene oxide and sulfur are added for high-speed shearing and stirring. The speed of the high-speed shearing machine is 3000 rpm, and the shearing time is 60 minutes; the stirrer stirs at a speed of 1000 rpm for 60 minutes. Then, liquid rubber is added, stirred at a speed of 1000 rpm for 30 minutes, and then left to stand for 4 hours to allow the modifier to swell, and then sulfonated kerosene is added for dilution, and stirred at a speed of 1000 rpm for 30 minutes to obtain a waterproof bonding layer material.

[0090] Comparative Example 3

[0091] This comparative example is a multi-component waterproof adhesive layer, which is prepared from the following raw materials in parts by weight: Component A:

[0092]

[0093] Component B:

[0094]

[0095] Component C:

[0096] Trimellitic anhydride

[0097] The weight ratio of component A to component B is 1:1.2, and the weight of component C is 3% of that of component B.

[0098] The preparation method is as follows:

[0099] After heating petroleum asphalt to 160°C, butadiene-styrene-butadiene block copolymer, polyethylene oxide and sulfur are added for high-speed shearing and stirring treatment. The speed of the high-speed shearing machine is 3000 rpm, and the shearing treatment time is 60 minutes; the stirrer is stirred at a uniform speed of 1000 rpm for 60 minutes. Then add liquid rubber, stir at a uniform speed of 1000 rpm for 30 minutes, stand for 4 hours to allow the modifier to swell, then add sulfonated kerosene for dilution, stir at a uniform speed of 1000 rpm for 30 minutes, and obtain component A. Dissolve stearic acid in anhydrous ethanol to form a transparent stearic acid anhydrous ethanol solution. Then add nano zinc oxide powder to the stearic acid anhydrous ethanol solution, disperse it for 10 minutes using an ultrasonic disperser, add epoxy resin, and stir at a uniform speed of 500 rpm for 10 minutes to obtain component B. Mix components A and B, heat to 50°C and stir. Component C was added and stirred at 800 rpm for 30 minutes. Finally, the mixture was heated to 50° C. for a second time and stirred at 600 rpm for 30 minutes to obtain a waterproof adhesive layer material.

[0100] Comparative Example 4

[0101] This comparative example is a multi-component waterproof adhesive layer, which is prepared from the following raw materials in parts by weight: Component A:

[0102]

[0103] Component B:

[0104]

[0105] Component C:

[0106] Pentaerythritol triallyl ether

[0107] Component D:

[0108] Trimellitic anhydride

[0109] The weight ratio of component A to component B is 1:1.2, the weight of component C is 5% of component A, and the weight of component D is 3% of component B.

[0110] The preparation method is as follows:

[0111] After heating petroleum asphalt to 160°C, butadiene-styrene-butadiene block copolymer, polyethylene oxide and sulfur are added for high-speed shearing and stirring. The speed of the high-speed shearing machine is 3000 rpm, and the shearing time is 60 minutes; the stirrer is stirred at a uniform speed of 1000 rpm for 60 minutes. Then add liquid rubber, stir at a uniform speed of 1000 rpm for 30 minutes, stand for 4 hours to allow the modifier to swell, then add sulfonated kerosene for dilution, stir at a uniform speed of 1000 rpm for 30 minutes, and obtain component A. Dissolve stearic acid in anhydrous ethanol to form a transparent stearic acid anhydrous ethanol solution. Then add nano zinc oxide powder to the stearic acid anhydrous ethanol solution, stir and disperse with a stirrer for 10 minutes, add epoxy resin, and stir at a uniform speed of 500 rpm for 10 minutes to obtain component B. Mix components A and B, heat to 50°C and stir. Component C was added and stirred at 800 rpm for 30 minutes, and then component D was added and stirred for another 30 minutes. Finally, the mixture was heated to 50° C. for a second time and stirred at 600 rpm for 30 minutes to obtain a waterproof adhesive layer material.

[0112] Comparative Example 5

[0113] This comparative example is a multi-component waterproof adhesive layer, which is prepared from the following raw materials in parts by weight: Component A:

[0114]

[0115] Component B:

[0116]

[0117] Component C:

[0118] Pentaerythritol triallyl ether

[0119] Component D:

[0120] Trimellitic anhydride

[0121] The weight ratio of component A to component B is 1:1.2, the weight of component C is 5% of component A, and the weight of component D is 3% of component B.

[0122] The preparation method is as follows:

[0123] After heating petroleum asphalt to 160°C, butadiene-styrene-butadiene block copolymer, polyethylene oxide and sulfur are added for high-speed shearing and stirring treatment. The speed of the high-speed shearing machine is 3000 rpm, and the shearing treatment time is 60 minutes; the stirrer is stirred at a uniform speed of 1000 rpm for 60 minutes. Then add liquid rubber, stir at a uniform speed of 1000 rpm for 30 minutes, stand for 4 hours to allow the modifier to swell, then add sulfonated kerosene for dilution, stir at a uniform speed of 1000 rpm for 30 minutes, and obtain component A. Dissolve stearic acid in anhydrous ethanol to form a transparent stearic acid anhydrous ethanol solution. Then add nano zinc oxide powder to the stearic acid anhydrous ethanol solution, disperse it for 10 minutes using an ultrasonic disperser, add epoxy resin, and stir at a uniform speed of 500 rpm for 10 minutes to obtain component B. Mix components A and B, heat to 50°C and stir. Component C was added and stirred at 800 rpm for 30 minutes, and then component D was added and stirred for another 30 minutes. Finally, the mixture was heated to 50° C. for a second time and stirred at 600 rpm for 30 minutes to obtain a waterproof adhesive layer material.

[0124] Comparative Example 6

[0125] This comparative example is a multi-component waterproof adhesive layer, which is prepared from the following raw materials in parts by weight: Component A:

[0126]

[0127] Component B:

[0128]

[0129] Component C:

[0130] Pentaerythritol triallyl ether

[0131] Component D:

[0132] Trimellitic anhydride

[0133] The weight ratio of component A to component B is 1:2, the weight of component C is 5% of component A, and the weight of component D is 3% of component B.

[0134] The preparation method is consistent with that of Comparative Example 5.

[0135] Comparative Example 7

[0136] This comparative example is a multi-component waterproof adhesive layer, which is prepared from the following raw materials in parts by weight: Component A:

[0137]

[0138] Component B:

[0139]

[0140] Component C:

[0141] Pentaerythritol triallyl ether

[0142] Component D:

[0143] Trimellitic anhydride

[0144] The weight ratio of component A to component B is 1:1.2, the weight of component C is 5% of component A, and the weight of component D is 3% of component B.

[0145] The preparation method is consistent with Comparative Example 5, but lacks the final preheating and stirring steps:

[0146] After heating petroleum asphalt to 160°C, butadiene-styrene-butadiene block copolymer, polyethylene oxide and sulfur are added for high-speed shearing and stirring treatment. The speed of the high-speed shearing machine is 3000 rpm, and the shearing treatment time is 60 minutes; the stirrer is stirred at a uniform speed of 1000 rpm for 60 minutes. Then add liquid rubber, stir at a uniform speed of 1000 rpm for 30 minutes, stand for 4 hours to allow the modifier to swell, then add sulfonated kerosene for dilution, stir at a uniform speed of 1000 rpm for 30 minutes, and obtain component A. Dissolve stearic acid in anhydrous ethanol to form a transparent stearic acid anhydrous ethanol solution. Then add nano zinc oxide powder to the stearic acid anhydrous ethanol solution, disperse it for 10 minutes using an ultrasonic disperser, add epoxy resin, and stir at a uniform speed of 500 rpm for 10 minutes to obtain component B. Mix components A and B, heat to 50°C and stir. Component C was added, and the mixture was stirred at 800 rpm for 30 minutes. Component D was then added, and the mixture was stirred for another 30 minutes to obtain a waterproof adhesive layer material.

[0147] Example 1

[0148] This comparative example is a fast-strengthening, long-lasting, high-toughness, high-elastic waterproof adhesive layer material, which is prepared from the following raw materials in parts by weight:

[0149] Component A:

[0150]

[0151] Component B:

[0152]

[0153] Component C:

[0154] Pentaerythritol triallyl ether

[0155] Component D:

[0156] Trimellitic anhydride

[0157] The weight ratio of component A to component B is 1:1.2, the weight of component C is 5% of component A, and the weight of component D is 3% of component B.

[0158] The preparation method is as follows:

[0159] After heating petroleum asphalt to 160°C, butadiene-styrene-butadiene block copolymer, polyethylene oxide and sulfur are added for high-speed shearing and stirring. The speed of the high-speed shearing machine is 3000 rpm, and the shearing time is 60 minutes; the stirrer is stirred at a uniform speed of 1000 rpm for 60 minutes. Then add liquid rubber, stir at a uniform speed of 1000 rpm for 30 minutes, stand for 24 hours to allow the modifier to swell, then add sulfonated kerosene for dilution, stir at a uniform speed of 1000 rpm for 30 minutes, and obtain component A. Dissolve stearic acid in anhydrous ethanol to form a transparent stearic acid anhydrous ethanol solution. Then add nano zinc oxide powder to the stearic acid anhydrous ethanol solution, disperse it for 10 minutes using an ultrasonic disperser, add epoxy resin, and stir at a uniform speed of 500 rpm for 10 minutes to obtain component B. Mix components A and B, heat to 50°C and stir. Component C was added and stirred at 800 rpm for 30 minutes, and then component D was added and stirred for another 30 minutes. Finally, the mixture was heated to 50° C. for a second time and stirred at 600 rpm for 30 minutes to obtain a waterproof adhesive layer material.

[0160] Example 2

[0161] This comparative example is a fast-strengthening, long-lasting, high-toughness, high-elastic waterproof adhesive layer material, which is prepared from the following raw materials in parts by weight:

[0162] Component A:

[0163]

[0164] Component B:

[0165]

[0166] Component C:

[0167] Pentaerythritol triallyl ether

[0168] Component D:

[0169] Trimellitic anhydride

[0170] The weight ratio of component A to component B is 1:1.2, the weight of component C is 5% of component A, and the weight of component D is 3% of component B.

[0171] The preparation method is consistent with that in Example 1.

[0172] Example 3

[0173] This comparative example is a fast-strengthening, long-lasting, high-toughness, high-elastic waterproof adhesive layer material, which is prepared from the following raw materials in parts by weight:

[0174] Component A:

[0175]

[0176] Component B:

[0177]

[0178] Component C:

[0179] Pentaerythritol triallyl ether

[0180] Component D:

[0181] Trimellitic anhydride

[0182] The weight ratio of component A to component B is 1:1.2, the weight of component C is 5% of component A, and the weight of component D is 3% of component B.

[0183] The preparation method is consistent with that in Example 1.

[0184] Example 4

[0185] This comparative example is a fast-strengthening, long-lasting, high-toughness, high-elastic waterproof adhesive layer material, which is prepared from the following raw materials in parts by weight:

[0186] Component A:

[0187]

[0188] Component B:

[0189]

[0190] Component C:

[0191] Pentaerythritol triallyl ether

[0192] Component D:

[0193] Trimellitic anhydride

[0194] The weight ratio of component A to component B is 1:1.5, the weight of component C is 5% of component A, and the weight of component D is 3% of component B.

[0195] The preparation method is consistent with that in Example 1.

[0196] Example 5

[0197] This comparative example is a fast-strengthening, long-lasting, high-toughness, high-elastic waterproof adhesive layer material, which is prepared from the following raw materials in parts by weight:

[0198] Component A:

[0199]

[0200]

[0201] Component B:

[0202]

[0203] Component C:

[0204] Pentaerythritol triallyl ether

[0205] Component D:

[0206] Trimellitic anhydride

[0207] The weight ratio of component A to component B is 1:1.2, the weight of component C is 5% of component A, and the weight of component D is 3% of component B.

[0208] The preparation method is the same as in Example 1, but the standing swelling time after adding the liquid rubber is 4 hours:

[0209] After heating petroleum asphalt to 160°C, butadiene-styrene-butadiene block copolymer, polyethylene oxide and sulfur are added for high-speed shearing and stirring treatment. The speed of the high-speed shearing machine is 3000 rpm, and the shearing treatment time is 60 minutes; the stirrer is stirred at a uniform speed of 1000 rpm for 60 minutes. Then add liquid rubber, stir at a uniform speed of 1000 rpm for 30 minutes, stand for 4 hours to allow the modifier to swell, then add sulfonated kerosene for dilution, stir at a uniform speed of 1000 rpm for 30 minutes, and obtain component A. Dissolve stearic acid in anhydrous ethanol to form a transparent stearic acid anhydrous ethanol solution. Then add nano zinc oxide powder to the stearic acid anhydrous ethanol solution, disperse it for 10 minutes using an ultrasonic disperser, add epoxy resin, and stir at a uniform speed of 500 rpm for 10 minutes to obtain component B. Mix components A and B, heat to 50°C and stir. Component C was added and stirred at 800 rpm for 30 minutes, and then component D was added and stirred for another 30 minutes. Finally, the mixture was heated to 50° C. for a second time and stirred at 600 rpm for 30 minutes to obtain a waterproof adhesive layer material.

[0210] Example 6

[0211] This comparative example is a fast-strengthening, long-lasting, high-toughness, high-elastic waterproof adhesive layer material, which is prepared from the following raw materials in parts by weight:

[0212] Component A:

[0213]

[0214] Component B:

[0215]

[0216] Component C:

[0217] Pentaerythritol triallyl ether

[0218] Component D:

[0219] Trimellitic anhydride

[0220] The weight ratio of component A to component B is 1:1.2, the weight of component C is 5% of component A, and the weight of component D is 3% of component B.

[0221] The preparation method is the same as that in Example 1, but in the process of preparing component B, the dispersion time using an ultrasonic instrument is 15 minutes:

[0222] After heating petroleum asphalt to 160°C, butadiene-styrene-butadiene block copolymer, polyethylene oxide and sulfur are added for high-speed shearing and stirring. The speed of the high-speed shearing machine is 3000 rpm, and the shearing time is 60 minutes; the stirrer is stirred at a uniform speed of 1000 rpm for 60 minutes. Then add liquid rubber, stir at a uniform speed of 1000 rpm for 30 minutes, stand for 24 hours to allow the modifier to swell, then add sulfonated kerosene for dilution, stir at a uniform speed of 1000 rpm for 30 minutes, and obtain component A. Dissolve stearic acid in anhydrous ethanol to form a transparent stearic acid anhydrous ethanol solution. Then add nano zinc oxide powder to the stearic acid anhydrous ethanol solution, disperse it for 15 minutes using an ultrasonic disperser, add epoxy resin, and stir at a uniform speed of 500 rpm for 10 minutes to obtain component B. Mix components A and B, heat to 50°C and stir. Component C was added and stirred at 800 rpm for 30 minutes, and then component D was added and stirred for another 30 minutes. Finally, the mixture was heated to 50° C. for a second time and stirred at 600 rpm for 30 minutes to obtain a waterproof adhesive layer material.

[0223] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

[0224] The performance of the waterproof adhesive materials obtained in Comparative Examples 1 to 7 and Examples 1 to 6 was tested. In Comparative Example 1, butadiene-styrene-butadiene block copolymer and liquid rubber were not added; in Comparative Example 2, only a single component A was used; in Comparative Example 3, component C was not added; in Comparative Example 4, component B was not dispersed by ultrasonic dispersion, but by ordinary mechanical stirring dispersion; in Comparative Example 5, the amount of petroleum asphalt in component A was different from the protection scope of the present invention; in Comparative Example 6, the relative ratio of component A to component B was different from the protection scope of the present invention; in Comparative Example 7, after all components were added and stirred, no secondary heating and stirring were performed.

[0225] The difference between Examples 1 to 4 is that the amounts of butadiene-styrene-butadiene block copolymer, liquid rubber, epoxy resin, and nano zinc oxide powder are different, and the blending ratios of components A and B are different; the difference between Example 5 is that the swelling time of component A is different; the difference between Example 6 is that the time for ultrasonic dispersion of component B is different.

[0226] For the waterproof adhesive layer materials of Comparative Examples 1-7 and Examples 1-6, the detection method is as follows:

[0227] (1) Test the performance indicators of the waterproof bonding layer in accordance with the requirements of the JC / T975-2005 standard for waterproof coatings for roads and bridges.

[0228] (2) According to the rotational viscosity test in the "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" JTGE20-2011.

[0229] (3) Rutting test was carried out in accordance with the "Testing Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" JTGE20-2011 (T0719-2011). The commonly used SMA-13 ​​asphalt mixture was used, and the mass ratio of waterproof bonding material to stone was 6.5%.

[0230] Table 1 Comparison of performance test results of comparative examples 1 to 7 and embodiments 1 to 6

[0231]

[0232]

[0233]

[0234] From the comparison of Examples 1-6 and Comparative Examples 1-7 in Table 1, it can be seen that the preparation process of the present invention is used to prepare a fast-strengthening, long-lasting, high-toughness and high-elastic waterproof bonding layer material, which has significantly superior performance compared to materials such as ordinary polymer-modified waterproof asphalt bonding layers. Specifically, it has high viscosity, high elasticity and tensile properties, excellent flexibility even at low temperatures, significantly higher bonding strength with the base layer, and outstanding waterproof performance. In addition, it can be cured and reach working strength in a short time, greatly shortening the time required for construction. The asphalt mixture specimen prepared using the waterproof bonding layer of the present invention has significantly better high-temperature rutting resistance than asphalt mixtures prepared from other asphalt materials.

[0235] In summary, the construction process of the fast-strength, long-lasting, high-toughness and high-elastic waterproof bonding layer material prepared by the technology of the present invention is relatively simple and quick, can be quickly cured and reach high strength, exhibits the characteristics of high viscosity, high elasticity and high durability, and can be widely used in road bonding layer construction and building waterproofing projects.

Claims

1. A fast-strengthening, long-lasting, high-toughness, high-elastic waterproof adhesive layer material, characterized in that: The raw materials include the following components in parts by weight: Component A: Component B: Component C: Pentaerythritol triallyl ether; Component D: Trimellitic anhydride; The weight ratio of component A to component B is 1:1.2-1:1.5, the weight of component C is 5% of component A, and the weight of component D is 3%-5% of component B.

2. The fast-strengthening, long-lasting, high-toughness, high-elastic waterproof adhesive layer material according to claim 1, characterized in that: The butadiene-styrene-butadiene block copolymer is a linear butadiene-styrene-butadiene block copolymer with a molecular weight of 80,000-100,000, and the molecular weight of polyethylene oxide is 20,000-40,000.

3. The fast-strengthening, long-lasting, high-toughness, high-elastic waterproof adhesive layer material according to claim 2, characterized in that: The stabilizer in component A is sulfur.

4. The fast-strengthening, long-lasting, high-toughness, high-elastic waterproof adhesive layer material according to claim 1, characterized in that: The liquid rubber in the component A is liquid butyl rubber with a molecular weight of 50,000 to 60,000.

5. The fast-strengthening, long-lasting, high-toughness, high-elastic waterproof adhesive layer material according to claim 1, characterized in that: The average particle size of the nano zinc oxide powder in component B is 16-18 nm.

6. A method for preparing a fast-strengthening, long-lasting, high-toughness, high-elastic waterproof adhesive layer material, characterized in that: The following steps are involved: (1) After heating petroleum asphalt, butadiene-styrene-butadiene block copolymer, polyethylene oxide and sulfur are added to perform high-speed shearing and stirring treatment; (2) adding liquid rubber to the material obtained in step (1) and stirring the mixture, and then standing the mixture to develop and swell; (3) adding sulfonated kerosene to the material obtained in step (2), stirring and diluting the mixture to obtain component A; (4) dissolving stearic acid in anhydrous ethanol to form a transparent stearic acid anhydrous ethanol solution, and then adding nano zinc oxide powder to the stearic acid anhydrous ethanol solution for dispersion; (5) adding epoxy resin to the milky white hydrophobic material solution formed in step (4), stirring, to obtain component B; (6) Components A and B are mixed, heated and stirred, then component C is added and stirred, and then component D is added and stirred again. (7) The material obtained in step (6) is heated and stirred for a second time, and a portion of the sulfonated kerosene is pre-evaporated to obtain the fast-strengthening, long-lasting, high-toughness, and high-elastic waterproof adhesive layer material.

7. The method for preparing a fast-strengthening, long-acting, high-toughness and high-elastic waterproof adhesive layer material according to claim 6, characterized in that: In step (1), the heating temperature is 150-160° C., the rotation speed of the high-speed shearing machine is 3000-4000 rpm, and the shearing treatment time is 60-80 minutes; the stirrer stirs at a speed of 1000-2000 rpm for 40-60 minutes; In step (2), the stirrer stirs at a speed of 1000 rpm for 20 to 40 minutes; the standing and swelling time is at least 2 hours; In step (3), the stirrer stirs at a speed of 1000 to 1200 rpm for 20 to 40 minutes; In step (4), the dispersion method is to use an ultrasonic disperser for dispersion, and the dispersion time is 10-15 minutes; In step (5), the mixer is stirred at a speed of 400-600 rpm for 10 minutes; In step (6), the heating temperature is 50-60°C, and the stirring time of component C and component D in the stirrer is 30 minutes respectively, and the stirring speed is 600-800 rpm; In step (7), the secondary heating temperature is 50° C., and the stirrer stirs at a speed of 600-800 rpm for 30 minutes.